Prostate cancer, exercise, and the heart: therapeutic implications & cardiovascular complications - Baumfalk, Dryden Ray (Kansas State University, 2022)
Current projections for 2021 indicate ~1.8 million individuals will be diagnosed with non-skin cancer in the United States. Of those, over 800,000 will be men with over 20% of them being new prostate cancer diagnosis. Prostate cancer is often slow growing and can go undetected for years and may not be medically treated when found if low disease progression is exhibited. Specific to the tumor, these solid tumor’s ability to adapt and resist therapy cornerstones such as radiation, that over 75% of all cancer patients receive, makes them difficult to treat in advanced disease. Prostate cancer specifically is a solid tumor that is known for the staples of hypoxia, necrosis, aberrant unfunctional vasculature, that lead to treatment resistance. In the following experiments presented in my dissertation, we investigate these challenges to treatment using an orthotopic model of prostate cancer in rats utilizing multiple cell lines that have similar characteristics as human prostate cancer. Due to preliminary data indicating the ability of chronic aerobic exercise to mitigate regions of hypoxia, in chapter one we sought to determine the distinct changes in tumor hypoxia and cell death to both moderate, high-intensity exercise training regimens in both the core and periphery of tumors. Further, we sought to test the possibility of improved radiosensitivity following both a moderate exercise training regimen, and a single acute bout of exercise in (Chapter 2). We found that both moderate, high intensity exercise training protocols can mitigate tumor hypoxia and improve markers of cell death. Subsequently, when exposed to a single 2gy dose of radiation, both moderate exercise training, and a single acute bout of exercise were able to increase radiosensitivity in tumor bearing rats. Outside of tumor specific responses to exercise, approximately 40% of patients with cancer report symptoms of fatigue, however, elucidating mechanisms of fatigue or atrophy with cancer versus concurrent adjuvant therapies is difficult, as withholding treatment to study the independent effects of cancer would be unethical. Given cancer-related fatigue or cardiovascular abnormalities can compromise the completion of anti-cancer treatment regimes, it is clinically important to understand how cancer affects determinants of exercise capacity (e.g., cardiac mass and function and skeletal muscle mass). Prior work has shown that prostate cancer in an orthotopic model, can induce cardiac atrophy in the absence of anti-cancer therapies. The ability of moderate intensity exercise training was able to prevent this, however, this led to the hypothesis for the third investigation that high-intensity aerobic exercise training can prevent heart and skeletal muscle atrophy associated with prostate cancer. We found that that high intensity exercise training regime was able to prevent cardiac atrophy associated with prostate cancer, in a shorter time frame than moderate intensity exercise. The product of these three investigations provide insights into the impact of exercise on both treatment, and prevention of cardiac dysfunction in a rat orthotopic model of prostate cancer.
Keywords: Prostate cancer; Exercise; Cardiovascular health; Radiation therapy; Atrophy